2019
DOI: 10.3389/fgene.2019.00514
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin as an Alternative Epigenetic Modulator: Mechanism of Action and Potential Effects

Abstract: Curcumin (a polyphenolic compound in turmeric) is famous for its potent anti-inflammatory, anti-oxidant, and anti-cancer properties, and has a great potential to act as an epigenetic modulator. The epigenetic regulatory roles of curcumin include the inhibition of DNA methyltransferases (DNMTs), regulation of histone modifications via the regulation of histone acetyltransferases (HATs) and histone deacetylases (HDACs), regulation of microRNAs (miRNA), action as a DNA binding agent and interaction with transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
141
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(150 citation statements)
references
References 186 publications
2
141
0
7
Order By: Relevance
“…Extensive oncological research demonstrated that plant natural compounds may be effective in targeting epigenetic alterations associated with the cancer promotion and progression as well as the primary chemoprevention by affecting the carcinogenesis in early stages during initiation [167]. A great amount of phytochemicals exerted anticancer activities via modulation of PHMs, as was demonstrated mainly in in vitro as well as in vivo preclinical studies focusing on BC, PC, and CRC [14,118,133,141,142,146,157,160,172]. However, the usefulness of phytochemicals within clinical approaches is not sufficiently investigated in this topic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive oncological research demonstrated that plant natural compounds may be effective in targeting epigenetic alterations associated with the cancer promotion and progression as well as the primary chemoprevention by affecting the carcinogenesis in early stages during initiation [167]. A great amount of phytochemicals exerted anticancer activities via modulation of PHMs, as was demonstrated mainly in in vitro as well as in vivo preclinical studies focusing on BC, PC, and CRC [14,118,133,141,142,146,157,160,172]. However, the usefulness of phytochemicals within clinical approaches is not sufficiently investigated in this topic.…”
Section: Discussionmentioning
confidence: 99%
“…The analogical effects of GEN compared to 5Aza-C (phase II clinical trial) predicted GEN as a potential novel therapeutic drug for patients with PC [145]. Interestingly, CUR was documented as a regulator of many epigenetic pathways [15,146]. Zhao et al evaluated the impact of CUR on suppression of LNCaP cells via inhibition of the c-Jun-N-terminal kinase (JNK) signaling pathway.…”
Section: Prostate Cancermentioning
confidence: 99%
“…Therefore, it was supposed that the microbiome could yield active metabolites from curcumin. However, the mechanisms of action remain unclear; it probably possesses an epigenetic modulating power but to date only in vitro studies are in support of these important effects [70].…”
Section: Nutritional Supplementsmentioning
confidence: 99%
“…Curcumin is the main active component in turmeric which constitutes for approximately 2–5% of turmeric . Curcumin contains three main compounds—80% curcuminoid complex, 17% dimethoxy‐curcumin, and 3% bisdemethoxy‐curcumin . Research has demonstrated that curcumin possess health benefits due to its antioxidant, anti‐inflammatory, antibacterial, antiviral, antifungal activity, and anti‐tumor effects.…”
Section: Protective Actions Of Curcuminmentioning
confidence: 99%